Effect of silicon on the alleviation of boron toxicity in wheat growth, boron accumulation, photosynthesis activities, and oxidative responses. (21st October 2017) - Liu, Chunguang; Lu, Wenkai; Ma, Qingna; Ma, Chengcang
ABSTRACT: Little is known about the alleviation of boron (B) toxicity in wheat induced by silicon (Si), especially on the photosynthesis properties and antioxidative responses. The purpose of this research was to evaluate the effect of Si on the toxicity of B in wheat and the related mechanisms. A greenhouse pot experiment was conducted using wheat ( Triticum aestivum Linn.) at the early seedling stage. Boric acid was added to soil to create three B concentrations. Each B treatment consisted of two Si treatment including control and Si application. Our results show that Si has an alleviative effect on B toxicity in wheat plant. Si showed significant alleviative effect on wheat growth at 150 mg B kg −1 whereas did not show significant alleviative effect at 300 mg B kg −1 . Under B stress, plant dry weight of wheat was reduced and the reduction was alleviated by Si. However, plant tissue B accumulation was not reduced by the application of Si. Net photosynthetic rates of wheat were not influenced significantly by B or Si. The oxidative damages in wheat that were caused by excess B were not significantly alleviated by Si. These results suggest that the effect of Si on B toxicity in wheat is still controversial and more studies need to be conducted.